POLYTECHNIC LEADERSHIP STRATEGIES IN IMPROVING LECTURERS PROFESSIONAL (Case Study at the Jakarta LP3I Polytechnic) - D. Punomo, D. Punomo; Wasliman, Iim; Kartika A.F., Ikka; Ratnawulan, Teti (IJOSMAS, 2021)
Polytechnic as one part of higher education which is regulated in Government Regulation Number 4 of 2014 concerning the Implementation of Higher Education and Management of Higher Education, is a university that organizes vocational education in various science and/or technology clusters and if it meets the requirements, polytechnics can organize professional education. LP3I Jakarta Polytechnic as one of the providers of vocational education with a number of students of approximately 5,000 students with a total of 296 teaching staff or permanent lecturers. Of the number of lecturers, there are still many who are not professional. Professional lecturers, in this study include; competence, lecturer tridharma, and lecturer certification. The method used in this research is a case study. The case study method is a method that is carried out directly in the actual process being studied, while the data obtained are not only from the data being studied, but also can be obtained from all parties who know and know the case. from various sources but limited in the cases to be studied. Based on the results of the research, the polytechnic leadership strategy in professional improvement of lecturers at the LP3I Jakarta Polytechnic has been running, namely through the polytechnic leadership strategy which is poured into the work program and action plans of each related leader according to their duties and functions. This can be seen from the increase in the number of lecturers who continue their education from S1 to S2, the evaluation of lecturer feedback has increased, the number of lecturers who get lecturer positions has increased and the number of lecturers who carry out research and community service has also increased. However, in its implementation it has not been fully implemented due to the constraints faced by each relevant leadership, especially the limited human resources, infrastructure and development budget for the professional improvement of the lecturers. And in general, the effectiveness of professional improvement strategies has increased but has not been achieved optimally